(untitled) (Lectio: Journal of Language and Language Teaching, 2021)
COVID-19 has caused a crisis in all sectors of life, including in the education sector. The COVID-19 pandemic forced the educators to find best strategy to save the nations’ education crisis. This study attempts to investigate EFL Indonesian teachers’ teaching strategy as well as to explore their challenges in adapting to the new mode of teaching during COVID-19. The application of online teaching in Indonesia has experienced several serious problems due to the unequal distribution of technology resources in all places in Indonesia. Therefore, improvisations in teaching are necessary so that every student in Indonesia can continue learning during this pandemic. Two EFL teachers from different regions in Indonesia were interviewed to find out about their English teaching strategies applied during the COVID-19 pandemic and their challenges in adapting to the new mode of teaching (distance education). This study also discussed the teachers’ efforts to overcome the challenges in teaching with a new mode. It is hoped that others can learn from the participants’ experience so that they will be more prepared to face the extension of the new learning mode.